2020
DOI: 10.1111/apa.15098
|View full text |Cite
|
Sign up to set email alerts
|

Providing a framework of principles for conceptualising the Fontan circulation

Abstract: The Fontan operation remains the final palliation for thousands of patients with complex congenital heart disease. By creating a Fontan circuit, control of cardiac output and congestion is wrested away from the ventricle and new haemodynamic forces take control. Understanding how to control the flow in the Fontan circuit will enable clinicians to improve patient management and possibly prevent future complications. Conclusion This review proposes a framework of principles to conceptualise the functionality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 22 publications
0
55
0
1
Order By: Relevance
“…Conversely, one study found a positive correlation between age at Fontan completion, and percent predicted peak VO 2 ( 30 ). Although later age at Fontan completion is accompanied by an extended period of volume overload and cyanosis, it may allow for pulmonary artery catch-up growth and a larger conduit to optimize flow ( 31 , 32 ); however, this theory requires verification.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, one study found a positive correlation between age at Fontan completion, and percent predicted peak VO 2 ( 30 ). Although later age at Fontan completion is accompanied by an extended period of volume overload and cyanosis, it may allow for pulmonary artery catch-up growth and a larger conduit to optimize flow ( 31 , 32 ); however, this theory requires verification.…”
Section: Discussionmentioning
confidence: 99%
“…This creates an unphysiological circulation with many potential problems. [19][20][21][22] The single pumping ventricle has to provide enough blood flow energy to perfuse the systemic as well as pulmonary vascular beds. This entails increased afterload for the ventricle and significantly increased systemic venous pressure and venous congestion in most organs.…”
Section: The Fontan Circul Ati Onmentioning
confidence: 99%
“…After the Fontan operation, the ventricle is volume deprived with limited ability to increase stroke volume. 21,39 The abnormal shape and function of the ventricle can lead to myocardial inflammation and fibrosis, further reducing output. Heart failure with low output and venous congestion becomes symptomatic, but the common underlying mechanism may be a slowly progressing pulmonary vascular resistance.…”
Section: F I G U R E 1 Illustrations Of Surgical Palliation Of Univentricular Heart Defects Bidirectional Glenn (A) With Anastomosis Of Tmentioning
confidence: 99%
“…However, the risks of mortality and morbidity remain high in these patients. This review by Gewillig et al 7 proposes a framework of principles to conceptualise the functionality and limitations of a Fontan circulation.…”
Section: A Framework Of Principles For Conceptualising the Fontal Circulationmentioning
confidence: 99%